Marine litter from fishery activities in the Western Mediterranean sea: The impact of entanglement on marine animal forests. (June 2019) - Consoli, Pierpaolo; Romeo, Teresa; Angiolillo, Michela; Canese, Simonepietro; Esposito, Valentina; Salvati, Eva; Scotti, Gianfranco; Andaloro, Franco; Tunesi, Leonardo
Abstract: The anthropogenic marine debris, especially abandoned, lost or otherwise discarded Fishing Gear (ALDFG), represents a rising concern, because of its potential harmful impact on the marine animal forests. We carried out 13 km of video recordings, by means of a remotely operated vehicle, from 10 to 210 m depth, in an anthropised area of the Tyrrhenian Sea (Mediterranean Sea). This site, for its high ecological importance and biodiversity value, has been identified for the establishment of a new marine protected area (MPA). The aim of this paper was to assess marine litter abundance and its effects on the benthic fauna. The debris density, in the study area, ranged from 0.24 to 8.01 items/100 m 2, with an average of 3.49 (±0.59) items/100 m 2 . The derelict fishing gear, mainly fishing lines, were the main source of marine debris, contributing 77.9% to the overall litter. The impacts of debris on the benthic fauna were frequently recorded, with 28.5% of the litter entangling corals and impacting habitats of conservation concern. These impacts were exclusively caused by the derelict fishing gear (91.2% by longlines), and the highest percentage (49.1%) of ALDFG causing impacts was observed from 41 to 80 m depth, in the coralligenous biocenosis. The results of the present study will help the fulfilment of "harm" monitoring, as recommended by the Marine Strategy Framework Directive (MSFD) and the UN Environment/MAP Regional Plan on the marine litter management in the Mediterranean Sea. Regarding the actions to reduce the derelict fishing gear, preventive measures are usually preferred instead of the extensive removals based on cost-effectiveness and sustainability. The establishment of a new MPA in the area could be a good solution to reduce ALDFG, resulting in the improvement of the ecological status of this coastal area. Graphical abstract: Image 1 Highlights: Marine litter was quantified within a new Marine Protected Area. Litter density ranged from 0.24 to 8.01 items/100 m 2 (mean = 3.49 items/100 m 2 ). Derelict fishing gear represented 77.9% of the total litter items. Fishing lines have been recognized as a cause of coral damage. Abstract : The derelict fishing gear, mostly fishing lines, were the main source of marine debris, contributing 77.9% to the overall litter observed in the Milazzo Marine Protected Area.